The formation of an economist - HICKS, J. (PSL Quarterly Review, 2013)
This is the first in a series of recollections by distinguished economists commissioned by the Banca Nazionale del Lavoro Quarterly Review. In it John Hicks reflects on his life, career and intellectual development. JEL: B31